1 Records of the Governor and Company of the Massachusetts Bay 392 (1853) - (:unkn) unknown (My University, 1620)
"For such of or nation as sell munition, gunns, or other furniture, to arme the Indians against vs, or teach them the vse of armes, wee would haue yow to apphend them and send them prisons for England, where they will not escape severe punishmt, being expressly against the proclamacon."
Keywords: ENSLAVED PERSONS & OTHER MINORITIES